2017
DOI: 10.5380/ce.v22i4.51823
|View full text |Cite
|
Sign up to set email alerts
|

Fatores De Risco Para O Câncer De Próstata: População De Uma Unidade Básica De Saúde

Abstract: PROSTATE CANCER RISK FACTORS: POPULATION FROM A BASIC HEALTH UNITABSTRACT: The present investigation aimed to identify prostate cancer risk factors in men assisted in a basic health unit in the state of São Paulo in November 2015. It was a descriptive, cross-sectional and quantitative study, with a sample of 150 male users that went to the unit for a medical appointment and/or nursing care. The most relevant risk factors were age, level of education, sedentary lifestyle, consumption of alcohol, red meat, milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
34

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
0
5
0
34
Order By: Relevance
“…En el diagnóstico de la neoplasia, es necesario que los profesionales de enfermería actúen en el cuidado integral de estos pacientes, ayudando en la toma de decisiones y en la evaluación de las intervenciones realizadas, a fin de reducir su ansiedad y el miedo ante lo desconocido (20)(21) .…”
Section: Discussionunclassified
“…En el diagnóstico de la neoplasia, es necesario que los profesionales de enfermería actúen en el cuidado integral de estos pacientes, ayudando en la toma de decisiones y en la evaluación de las intervenciones realizadas, a fin de reducir su ansiedad y el miedo ante lo desconocido (20)(21) .…”
Section: Discussionunclassified
“…It is reported that Brazil has a high incidence of PC and in 2014, 68,800 new cases were estimated in the country. Numerous determinants of the disease are evident that influence its origin, severity and / or aggressiveness, such as advanced age, high rate of diagnosis, lifestyle, endocrine and environmental conditions, [4][5][6][7][8] as well as family history, which has the potential to increase the chances of developing cancer by up to ten times. 4 It is recorded that, around 75% of PC diagnoses worldwide occur in economically developed countries.…”
Section: Original Articlementioning
confidence: 99%
“…It is revealed that, in recent years, PC has become an important object of study among researchers considered references in the theme. 8 It is characterized by being a multifaceted and ascending issue that requires, therefore, expressive dedication of health professionals, especially nurses, to act in prevention, direct assistance and participation in planning and evaluation of men's health care, thus contemplating, the completeness of care. 4 It was evidenced in this study that the State of Bahia obtained the highest prevalence of hospitalizations (36.9%) and deaths (35.5%) and…”
Section: Total Valuementioning
confidence: 99%
“…1 Age is a considerable risk factor for some diseases, including Prostate Cancer (PC), being rare before the age of 40 and most common after 50 years old. 2 In Brazil, the biennial 2016/2017 estimate points to 600,000 new cases of cancer. This epidemiological profile is similar to that of Latin America and the Caribbean, with prostate cancer leading in the ranking of the most incidents in all regions of the country, with an estimated sixty-one thousand new cases.…”
Section: Introductionmentioning
confidence: 99%